Interrupted versus continuous suturing for vesicourethral anastomosis during radical prostatectomy: protocol for a systematic review and meta-analysis - Kowalewski, Karl-Friedrich; Hetjens, Svetlana; Nickel, Felix; Ritter, Manuel; Kriegmair, Maximilian (BMJ open, 2017)
Introduction Radical prostatectomy is the mainstay of treatment for prostate cancer. The vesicourethral anastomosis is a critical step, which most likely impacts urinary continence and urethral stenosis. To date, it still remains unclear whether interrupted and continuous suturing for the anastomosis have different outcomes. Therefore, the aim of this systematic review and meta-analysis is to compare different suture techniques for vesicourethral anastomosis in terms of surgical and functional parameters. Methods and analysis: A comprehensive literature search will be conducted covering MEDLINE, Embase, Web of Science, the Cochrane Central Register of Controlled Trials and ClinicalTrials.gov. Studies comparing interrupted versus continuous suturing will be included in the analyses. No language restrictions will be applied. Screening, data extraction, statistical analysis and reporting will be done in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Quality assessment will be performed with the help of the Cochrane Collaboration’s tool for assessing risk of bias and the Newcastle-Ottawa Scale for assessing quality of non-randomised studies. The quality of evidence will be evaluated with the Grading of Recommendations Assessment, Development and Evaluation. The primary outcome will be the time until removal of the urinary catheter. Secondary outcomes include rate of extravasation, length of hospital stay, time needed to perform the anastomosis, continence level at defined postoperative intervals and development of urethral strictures. Quantitative analysis will be calculated if meaningful. Ethics and dissemination: In order to meet the highest ethical and methodological standards. we followed the PRISMA Protocol 2015 checklist. Each item was answered appropriately. For systematic reviews the ethical issues are strictly methodological as only data that were published earlier will be used. The full manuscript will be submitted to a peer-reviewed journal. Furthermore, the results will be presented on national and international congresses. Trial registration number: International prospective register of systematic reviews PROSPERO CRD42017076126.
Gesehen am 12.04.2018